Thiopental Does Not Produce Hyperalgesia: A Laboratory Study Using Two Human Experimental Pain Models. Issue 11 (6th April 2020) - Arout, Caroline A; Petrakis, Ismene L; Ralevski, Elizabeth; Acampora, Gregory; Koretski, Julia; DeNegre, Diana; Newcomb, Jenelle; Perrino, Albert C
Abstract: Objective: Past investigations assessing the effects of thiopental on pain are conflicting. Although several studies demonstrate hyperalgesia as a result of barbiturate administration, others show analgesia. Our objective was to assess the effects of an infusion of the GABAA agonist thiopental, compared with placebo, in healthy participants on two subjective experimental pain paradigms: noxious electrical stimulation and intradermal capsaicin. Methods: For electrical stimulation, the milliamps required to achieve pain threshold and tolerance were recorded, and the percent change from baseline was determined for each infusion condition. In the intradermal capsaicin condition, the area of hyperalgesia was determined by von Frey technique pre- and postinfusion, and the percent change in the area of hyperalgesia was calculated. Results: Though thiopental infusion resulted in an increase in the electrical stimulation current required to elicit pain threshold or reach pain tolerance when compared with baseline, this finding was not statistically significant. In the intradermal capsaicin condition, there was a statistically significant difference in overall pre- and postinfusion pain interpretation, as measured by the McGill Pain Questionnaire ( P  <   0.05), but there was no significant difference in area of hyperalgesia. Conclusions: In this human study of thiopental's effects on two experimental pain models, our results show that thiopental does not induce hyperalgesia.